Strategi Pengelolaan Sumber Daya Manusia untuk Meningkatkan Produktivitas Karyawan pada Usaha Mebel Skala Kecil dan Menengah - Elsy Nila Sari Situmeang; Ellma Aggresia Br Purba; Aprilia Zaeni Rapiah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
Human resource (HR) management in small and medium scale furniture businesses has a crucial role as the main driver of business success, as well as making a significant contribution to the national economy through absorbing labor and increasing people's income. However, this sector faces various challenges, such as limited capital, technology and effective workforce management. In contrast to large companies, small and medium enterprises (SMEs) in the furniture sector have limitations in employee development due to limited financial resources, which has an impact on training, skills development and incentives. With increasing demands for globalization and digitalization, SMEs are required to adapt and optimize HR management to increase competitiveness. Therefore, a strategic approach in HR management, such as continuous training, performance evaluation, and implementation of a structured management system, is very important to increase employee productivity and work quality. This research aims to identify effective strategies that can optimize employee potential, increase business productivity, and have a positive impact on local economic growth. Implementation of the right strategy is expected to be able to improve the performance of furniture SMEs and the welfare of the workforce in a sustainable manner.